A new approach to Polioencephalomalacia (PEM) - B.E. Brent; K.S. Lusby; J.A. Kobuszewski; J.C. Parks (Kansas Agricultural Experiment Station Research Reports, 1972)
Polioencephalomalacia (PEM) is a disorder of the ruminant central nervous system characterized by sudden onset and rapid death. At autopsy, the brain may be swollen and cerebral cortex degenerated. Early symptoms may include disorientation and muscular in coordination. Affected animals may push against fences or other objects with their heads. More commonly, they are found dead or in a coma. If central nervous system damage is not excessive, animals with early symptoms respond to massive injections of thiamine, but may not recover coordination.
Keywords: Cattlemen& #x27; s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Polioencephalomalacia (PEM); Central nervous system; Rumen